A MONOGRAPH OF THE GENUS NEOCINNAMOMUM LIOU HO - KOSTERMANS, A. J. G. H. (REINWARDTIA, 1974)
The Asiatic Genus Neocinamomum comprises 6 species, of which N. atjehense is described here for the first time. cinnamomum fargesii Lee.is moved to Neocinnamomum,N. willsonii Allen is considered to be conspeeific with it. N. delavayi var.Mekongense hand.Mazz is raised to specific rank. N. hainanianum Allen is reduced to N.lecomtei.Excluded from the genus is N.confertiflorum, which is moved to Litsea.